Connexin 43 expression in human hypertrophied heart due to pressure and volume overload - Vetter, C; Zweifel, M; Zuppinger, C; Carrel, T; Martin, D; Haefliger, J. A; Delacrétaz, E (Physiological research, 2010)
Left ventricular hypertrophy (LVH) is due to pressure overload or mechanical stretch and is thought to be associated with remodeling of gap-junctions. We investigated whether the expression of connexin 43 (Cx43) is altered in humans in response to different degrees of LVH. The expression of Cx43 was analyzed by quantitative polymerase chain reaction, Western blot analysis and immunohistochemistry on left ventricular biopsies from patients undergoing aortic or mitral valve replacement. Three groups were analyzed: patients with aortic stenosis with severe LVH (n=9) versus only mild LVH (n=7), and patients with LVH caused by mitral regurgitation (n=5). Cx43 mRNA expression and protein expression were similar in the three groups studied. Furthermore, immunohistochemistry revealed no change in Cx43 distribution. We can conclude that when compared with mild LVH or with LVH due to volume overload, severe LVH due to chronic pressure overload is not accompanied by detectable changes of Cx43 expression or spatial distribution.
Keywords: Aged; Blood Pressure; regulace genové exprese; Ventricular Function, Left; RNA, Messenger; Aged, 80 and over; mitrální insuficience; imunohistochemie; stupeň závažnosti nemoci; Biopsy; Mitral Valve Insufficiency; messenger RNA; Hypertrophy, Left Ventricular; lidé; lidé středního věku; senioři; ženské pohlaví; polymerázová řetězová reakce s reverzní transkripcí; financování organizované; Blotting, Western; mužské pohlaví; western blotting; Female; konexin 43; Financing, Organized; Aortic Valve Stenosis; Myocardium; Middle Aged; myokard; Reverse Transcriptase Polymerase Chain Reaction; aortální stenóza; senioři nad 80 let; hypertrofie levé komory srdeční; Humans; Male; Gene Expression Regulation; biopsie; funkce levé komory srdeční; Immunohistochemistry; Severity of Illness Index; krevní tlak; Connexin 43